A Novel Complete Reading Embedded System for the Vision Impaired - Nazemi, Azadeh; Murray, Iain (Globle Science &technology Forum, 2012)
This paper, presents design and implementation of an embedded Complete Reading System to address the needs of vision impaired people to access and read electronic documents. The main aim of this research is approaching to design a standalone, low cost and affordable reading system for developing countries. Other factors considered within this research include portability, power consumption, multilingual ability and simplicity of use. To design this system Beagle Board (OMAP3530) an application processor board is considered as the hardware platform. The RC8660 is used as an integrated Text-to-Speech (TTS) processor to implement high quality, fully functional and multilingual TTS system.